Oncology drugs and added benefit: insights from 3 European health technology assessment agencies on the role of efficacy endpoints. (1st January 2022) - Smith, Nathaniel; Fu, An-Chen; Fisher, Tim; Meletiche, Dennis; Pawar, Vivek
Abstract: Objective: This study aimed to understand the impact of different efficacy endpoints on reimbursement decisions made by health technology assessment (HTA) bodies. Materials and methods: European Medicines Agency (EMA) oncology product marketing authorizations were screened to identify products that completed review by 3 HTA bodies during 2016–2019: United Kingdom's National Institute for Health and Care Excellence, Germany's Gemeinsamer Bundesausschuss, and France's Haute Autorité de Santé. Each decision's endpoint information, including overall survival (OS) and progression-free survival (PFS), was extracted. Each endpoint's influence on added benefits rating (the degree of added benefit as judged by the HTA agency) and full reimbursement (i.e. reimbursed population to label) decisions was tested using bivariate analyses. Results: An increasing trend was observed toward HTA submissions with immature OS data (36.8% and 71.4% in 2016 and 2019, respectively), which was a predictor of limited added benefit ( p < .001). Regarding data availability, 63% of submissions provided OS, 2% provided PFS without OS; and 35% provided neither. OS availability significantly influenced added benefit ( p < .001) but not full reimbursement ( p > .05) decisions, whereas PFS without OS had no significant impact compared with either OS or PFS data for either outcome ( p = .99). Conclusions: The trend toward fewer products filing mature OS data over time suggests sponsors may be increasingly confident achieving reimbursement with surrogate endpoint data, although mature OS data provided the strongest correlation to positive reimbursement decisions. Notably, in some locally advanced settings, OS data maturity will take a long time to obtain. To expedite patient access to new medicines, payers should consider the acceptance of surrogate endpoints predictive of clinical benefit.